A comparative utilisation of high dietary copra and palm kernel cakes-based diets with exogenous enzyme by young pullets and layers - diarra, siaka seriba (Indian Journal of Animal Nutrition, 2018)
The effects of enzyme supplementation of copra cake (CPC) and palm kernel cake (PKC) in growing pullets and laying hens were investigated in two experiments. In experiment 1 a control diet based on fish meal and soybean meal and 4 diets containing 200 g CPC or PKC/kg with and without exogenous enzyme were fed each to 3 replicate pens containing 10 growing pullets for a period of 70 days. In experiment 2 diets formulated as in experiment 1 were fed each to 10 point of lay birds for a period of 84 days. Pullets fed CPC and PKC based diets consumed more feed and water than the control (P